Evidence for a multilayered internal structure of the chondritic acapulcoite-lodranite parent asteroid. (1st December 2018) - Li, Shijie; Yin, Qing-Zhu; Bao, Huiming; Sanborn, Matthew E.; Irving, Anthony; Ziegler, Karen; Agee, Carl; Marti, Kurt; Miao, Bingkui; Li, Xiongyao; Li, Yang; Wang, Shijie
Abstract: We report a petrography, mineral chemistry, oxygen and chromium isotopic study of Grove Mountains (GRV) 020043 together with a subset of other acapulcoites and lodranites. GRV 020043 is a petrologic type 4 chondrite, with chondrules of diverse types and sizes, and is composed of low-Ca pyroxene (40 vol.%), olivine (24 vol.%), diopside (8 vol.%), plagioclase (10 vol.%), Fe-Ni metal (kamacite and taenite), troilite and some accessory minerals (chromite and apatite). The olivine in GRV 020043 has an average fayalite content (Fa) of 10.7 mol.% with the low-Ca pyroxene having an average ferrosilite content (Fs) of 10.8 mol.%. The whole rock oxygen isotopic composition of GRV 020043 is +3.226 ± 0.267‰, +0.797 ± 0.131‰, and −0.927 ± 0.017‰ for δ 18 O, δ 17 O, and Δ 17 O, respectively, with a bulk chromium isotopic compositions of ε 54 Cr = −0.48 ± 0.10. These characteristics of GRV 020043 are different from all established or ungrouped chondrites but agree with those of the acapulcoite-lodranite clan. We therefore suggest that GRV 020043 represents the chondritic precursor of acapulcoite-lodranite parent body. The similarity of bulk oxygen and chromium isotopic compositions among GRV 020043, Acapulco, Northwest Africa (NWA) 468 (metal-rich lodranite), NWA 8118 (lodranite), NWA 8287 (acapulcoite), and NWA 8422 (lodranite) indicates that they originated from a common oxygen and chromium reservoir in the protoplanetary disk or may have derived from a parent body with a differentiated multilayer structure.